Fikih Lingkungan - Muhammad Ghufron (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
This paper discusses the concept of environment in the perspective of Islamic law (fiqh). Understanding of environmental issues (fiqh al bi `ah) and the treatment needs to be placed on an ethical and moral foundation to support all efforts that have been made and nurtured during this even though it has not been able to cope with environmental degradation. Fiqh environment in order to awaken people of faith to realize that environmental issues are not released from the responsibility of man who is faithful and a mandate from Allah to preserve and protect nature from all sorts of damage and destruction that resulted in his own life-threatening. Environmental conservation law is fardlu kifayah. That is, all those individuals and groups responsible for environmental protection, and should be involved in the handling of environmental damage.